ANALISIS PENGARUH UPAH MINIMUM TERHADAP TINGKAT PENYERAPAN TENAGA KERJA DI KOTA PAREPARE TAHUN 2014-2018 - Pratama, Andi Ferry (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2021)
This research aims to determine the effect of the minimum wage on the absorption rate of labor in Parepare city in 2014- 2018. The types of data used in this study are quantitative data and qualitative data while the data sources are person, paper, and place. Data collection techniques used by observation and documentation. The data analysis technique used to process data is a simple linear regression formula. The results showed that the amount of the minimum wage of the City of Parepare in the last five years has always increased, the results of a simple linear regression analysis shows that there is no significant influence between the minimum wage and the absorption rate of the City of Parepare labor.